2019
DOI: 10.1371/journal.pone.0211710
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-resolved analysis of coherent oscillations of local cerebral blood volume, measured with near-infrared spectroscopy, and systemic arterial pressure in healthy human subjects

Abstract: We report a study on twenty-two healthy human subjects of the dynamic relationship between cerebral hemoglobin concentration ([HbT]), measured with near-infrared spectroscopy (NIRS) in the prefrontal cortex, and systemic arterial blood pressure (ABP), measured with finger plethysmography. [HbT] is a measure of local cerebral blood volume (CBV). We induced hemodynamic oscillations at discrete frequencies in the range 0.04–0.20 Hz with cyclic inflation and deflation of pneumatic cuffs wrapped around the subject’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…Notice that SDI has a consistent T / ABP relationship across all four subjects with a mean phase difference of −40° ± 4° and mean amplitude ratio of 0.037 ± 0.002 μM/mm Hg (5% error). This is within the range of values for T / ABP at 0.1 Hz reported recently by our group . However, the other analysis methods (SDϕ, SS and DS) do not show this consistent relationship and feature a large variance in some cases.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Notice that SDI has a consistent T / ABP relationship across all four subjects with a mean phase difference of −40° ± 4° and mean amplitude ratio of 0.037 ± 0.002 μM/mm Hg (5% error). This is within the range of values for T / ABP at 0.1 Hz reported recently by our group . However, the other analysis methods (SDϕ, SS and DS) do not show this consistent relationship and feature a large variance in some cases.…”
Section: Resultssupporting
confidence: 85%
“…The effect of this is seen in our T / ABP results in Section 3.2, where the most superficial methods (SDI) shows the most consistent relationship for T / ABP . Recently, our group presented a model based on these consistent T / ABP results measured with SDI . However, the results presented here do not show the same consistent T / ABP vector for deeper tissue, suggesting that the previous data and model may have been mostly representative of scalp hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Even more recently, we have investigated the frequency-resolved relationships between T and ABP and suggested that robust NIRS measurements of total hemoglobin concentration oscillations may be sensitive to the timing of cerebral BF dynamics and thus to cerebral autoregulation. 16 More precisely we have proposed a model for the transfer function between ABP and T which is composed of two terms: a frequency-independent term due to arterial compliance and a frequency-dependent term due to venous compliance that also reflects the dynamics of cerebral BF. The venous term has the structure of a low pass filter which depends on the oscillation frequency and two parameters, one of them being the cerebral autoregulation time constant [τ ðARÞ ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, we have also used CHS for estimating the transfer function between ABP and T, which may offer a more robust NIRS method (being based on high signal-to-noise measurements of total hemoglobin concentration dynamics) to assess cerebral autoregulation. 16 One well-known issue that needs to be addressed in noninvasive cerebral NIRS is the high sensitivity of optical signals to hemodynamics occurring in the superficial, extracerebral tissue layers (mainly scalp and skull). One common feature of many algorithms proposed in the literature to correct for the extracerebral contamination is to assume some level of independence of the hemodynamic changes in the brain and those in the scalp and skull.…”
Section: Introductionmentioning
confidence: 99%
“…While many different methods have been developed to study CA, there is no agreed upon "gold-standard" method for noninvasive evaluation of CA [15][16][17][18]. CA has been assessed by quantifying the relationships (gains) of spontaneous low-frequency oscillations (LFOs) between the mean arterial pressure (MAP) and cerebral hemodynamic parameters such as CBF and cerebral blood oxygenation [19]. In general, smaller LFO gains correspond to better CAs [20,21].…”
Section: Introductionmentioning
confidence: 99%